GEOCHEMISTRY AND SPECIFIC FEATURES OF MANGANESE ORE FORMATION IN SEDIMENTS OF OCEANIC BIOPRODUCTIVE ZONES - Dubinin A.V.; Uspenskaya T.Yu. (My University, 2006)
Processes of authigenic manganese ore formation in sediments of the northern equatorial Pacific are considered on the basis of study of the surface layer (<2 mm) of ferromanganese nodule and four micronodule size fractions from the associated surface sediment (0-7 cm). Inhomogeneity of the nodule composition is shown. The Mn/Fe ratio is maximal in samples taken from the lateral sectors of nodule at the water-sediment interface. Compositional differences of nodules are related to the preferential accumulation of microelements in iron oxyhydroxides (P, Sr, Pb, U, Bi, Th, Y, and REE), manganese hydroxides (Co, Ni, Cu, Zn, Cd, Mo, Tl, W), and lithogenous component trapped during nodule growth (Ga, Rb, Ba, and Cs). The Ce accumulation in the REE composition is maximal in the upper and lower parts of the nodule characterized by the minimal Mn/Fe values. The compositional comparison of manganese micronodules and surface layers of the nodule demonstrated that the micronodule material was subjected to a more intense reworking during the diagenesis of sediments. The micronodules are characterized by higher Mn/Fe and P/Fe ratios but lower Ni/Cu and Co/Ni ratios. The micronodules and nodules do not differ in terms of contents of Ce and Th that are least mobile elements during the diagenesis of elements. Differences in the chemical composition of micronodules and nodules are related not only to the additional input of Mn in the process of diagenesis, but also to the transformation of iron oxyhydroxides after the removal of Mn from the close association with Fe formed in the suspended matter at the stage of sedimentation. © Pleiades Publishing, Inc. 2006.